2013
DOI: 10.1186/2050-6511-14-61
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral brachial plexus injury following acute carbon monoxide poisoning

Abstract: BackgroundCarbon monoxide (CO) intoxication is a leading cause of severe neuropsychological impairments. Peripheral nerve injury has rarely been reported. It consists usually in a demyelinating polyneuropathy or mononeuropathy affecting mainly the lower limbs. Isolated involvement of both upper extremities has been described in only 4 patients related to root damage. We report the first case of bilateral brachial plexus injury following CO poisoning and review all previous CO-induced neuropathy described in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…Dennoch wurde in einigen Fallserien beschrieben, dass Neuropathien, Plexopathien oder Radikulopathien durchaus vorkommen können. [27]. Elektroneurographisch und histologisch handelt es sich dabei meist um demyelinisierende Neuropathien.…”
Section: Klinikunclassified
“…Dennoch wurde in einigen Fallserien beschrieben, dass Neuropathien, Plexopathien oder Radikulopathien durchaus vorkommen können. [27]. Elektroneurographisch und histologisch handelt es sich dabei meist um demyelinisierende Neuropathien.…”
Section: Klinikunclassified
“…[ 2 , 4 ] Choi [ 5 ] suggested that peripheral neuropathy is usually associated with local swelling secondary to muscle necrosis, which is an important factor contributing to the development of peripheral neuropathy after carbon monoxide intoxication. Rahmani et al [ 6 ] reported bilateral brachial plexus injury after carbon monoxide intoxication after failed use of a water heater. They attributed the bilateral plexopathy to a combination of ischemic and toxic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the occurrence of local swelling in 10 of these 20 patients and the occurrence of delayed neurological sequelae in 3 of 20 patients, complete recovery was achieved within 3 to 6 months in all patients. The patient reported by Rahmani et al, [ 6 ] who had been diagnosed with bilateral brachial plexus injury after carbon monoxide intoxication, was observed to recover without any sequelae within 4 months. Choi and Lim [ 15 ] reported a patient with peripheral neuropathy involving the bilateral lower extremities after carbon monoxide intoxication who did not develop local swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Direct signs of peripheral neuropathy are the changes of affected nerve itself, such as changes in signal intensity particularly high signal intensity on T2WI, variable but contrast enhancement in usual, increased diameter of nerve by swelling, morphologic distortion, etc. Indirect sign of involved muscle is characterized by increased muscle signal intensity on fluid-sensitive MR sequences as a result of acute or subacute denervation edema, which also may be an important contributing factor to the development of neuropathy (5). Sequentially the affected muscle may reveals increased signal intensity on T1WI with decreased volume due to fatty atrophic change (7,8).…”
Section: Dmentioning
confidence: 99%
“…Another case report of bilateral brachial plexus injury following acute CO intoxication by Rahmani et al (5) 42 years old male who showed a brachial diplegia and hypoesthesia had complete recovery of neurological disorders. On the other hand, Jeong et al (6) reported a case of bilateral femoral neuropathy after CO intoxication which showed persisted neuropathy with minor improvement.…”
Section: Dmentioning
confidence: 99%